Diversity of echinoderms of class echinoidea and holothuroidea in waingapu old pier, east sumba regency - Ferdinand Ndawa Lu Remindima; Erfy Melany Lalupanda; Anita Tamu Ina (STKIP Persada Khatulistiwa Sintang, 2021)
Echinoderms are in habitats in coastal waters because is a biota that can maintain the sustainability and the balance of the coral reef ecosystem. Human activity in utili zing Echinoderms, namely in Echinoidea and Holothuroidea can affect life his life. The purpose of this study was to determine the diversity of phyla Echinoderms class Echinoidea and Holothuroidea at the Harbor Waingapu Old Pier and its use as a medium Biology learning. The research method used is purposive sampling and analyzed using the approach quantitative descriptive with the Shannon diversity index formula Wiener. Echinoderm samples were calculated using the technique quadratic transects with a plot size of 2 x 2 meters are placed perpendicularly in the direction of 50 meters using a plot of 30 plot. Environmental factors measured are temperature, salinity, degrees acidity (pH) and levels of oxygen (DO). Measurements are taken at each observation station. The results showed 11 species Echinoderms are divided into 2 classes, namely Diadema setosum, Diadema savignyi, Tripneustes gratilla, Strongylocentrotus droebachiensis, Echinocardium flavescens, Clypeaster subdepressus, and Mespilia globulus from the class Echinoidea. Holothuria atra, Holothuria scraba, Euapta godeffroyi and Chiridota rigida from the class Holothuroidea. The diversity index obtained includes medium category with a value of H = 1.696.